Low-Density lipoprotein cholesterol goal achievement and associated factors among type 2 diabetes mellitus patients at Tikur Anbessa Specialized Hospital in Addis Ababa, Ethiopia: Cross-sectional Study, 2023 - Abdisa Beyene; Teshome Habte; Aklil Hailu (Elsevier, 2024)
Background: Achieving the recommended low-density lipoprotein cholesterol goal is vital for managing cardiovascular risk. However, research on low-density lipoprotein cholesterol goal achievement and associated factors in Sub-Saharan Africa, particularly in Ethiopia, is limited. While global rates vary from 18% to 73%, there is a need for further investigation in this region to better understand and address the factors influencing low-density lipoprotein cholesterol goal attainment.The objective was to assess low-density lipoprotein cholesterol goal achievement and associated factors among type 2 diabetes patients. Methods: Institution based quantitative cross-sectional study design was conducted among type II diabetes patients at Tikur Anbessa Specialized Hospital in Addis Ababa, Ethiopia.Systematic random sampling technique was used to select patient records. Data was collected by using a structured and pretested checklist and some variables were also collected from the chart review, structured questionnaire and analyzed using Epi info version 7.2 and SPSS version 25. Bivariate and multivariable logistic regressions were performed to examine the association between variables. Adjusted odds ratios (AOR) with 95 % confidence intervals were calculated, and a p-value of ≤ 0.05 was considered statistically significant for associations between independent and outcome variables. Result: The LDL goal achievement among type II diabetes patients is 58.9 %.Total triglyceride level (AOR = 0.19, 95 %CI, 0.12, 0.54, P= <0.0001), history of smoking (AOR = 0.198, 95 %CI, 1.06, 1.10, P < 0.0001), 40-65 years of age (AOR = 0.21, 95 %CI, 0.05, 0.87, P = 0.03), BMI (AOR = 0.19, 95 %CI, 0.12, 0.54, P= <0.0001)., were found to be statistically significant independent predictors for LDL Goal Achievement in type II Diabetes patients. Conclusion: In the current study, significant proportions of type II DM patients fail to attain acceptable levels of LDL cholesterol. Factors like total triglyceride levels, smoking history, older age, and increased BMI influenced low-density lipoprotein cholesterol goal achievement. Advanced in age, increase in BMI, smoking, and higher levels of triglyceride were determinants of LDL cholesterol goal achievement. Patient education on life style modification mainly cessation of smoking diet and exercise may be recommended to achieve the LDL cholesterol goal.